Petri nets teaching in the Mechatronics Engineering course - De Lemos, Marilza Antunes [UNESP]; Botura Jr., Galdenoro [UNESP]; Marques, Marcio Alexandre [UNESP] (Elsevier, 2007)
The current solutions implanted in the majority of manufacturing systems controlled by PLCs were developed through the language of programming known as ladder. Such a language, easily learned and handled, shows to be efficient whenever the system to be implanted does not demand greater complexity of analyses. Bigger systems, presenting characteristics in which resource compartments, parallelism and synchronizing among processes are more frequent, demand the adoption of solutions differentiation. This article presents a teaching experience and practical application of Petri nets in a Mechatronics Engineering graduation course. Copyright © 2007 IFAC.
Keywords: Discrete-events systems; Education; Mechatronic; Petri nets teaching; Programming; Simulation-supported learning; Application of Petri nets; Engineering course; Graduation course; Teaching experience; Cost effectiveness; Curricula; Mechatronics; Petri nets; Product development; Teaching; Technical presentations; Manufacture